Morpho-Phylogenetic Evidence Reveals New Species of Fuscosporellaceae and Savoryellaceae from Freshwater Habitats in Guizhou Province, China - Hong-Zhi Du; Jing Yang; Ning-Guo Liu; Ratchadawan Cheewangkoon; Jian-Kui Liu (Journal of Fungi, 2022)
During a survey of freshwater fungi in Guizhou Province, China, six hyphomycetous collections were founded on decaying wood from freshwater habitats. These taxa were characterized and identified based on morphology, phylogeny, and culture characteristics. Phylogenetic analysis of combined LSU, SSU, ITS, RPB2 and TEF1α sequence data indicated that our six isolates formed three distinct lineages and were distributed within Fuscosporellaceae and Savoryellaceae. They can be organized as three new species: Fuscosporella guizhouensis, Mucisporaaquatica and Neoascotaiwaniaguizhouensis. Fuscosporella guizhouensis and Neoascotaiwania guizhouensis have sporodochial conidiomata, micronematous conidiophores and dark brown conidia. The former possesses irregularly ellipsoidal conidia with apical appendages, while the latter has fusiform to obovoid conidia. Mucispora aquatica is characterized by macronematous conidiophores, elongating percurrently and dark brown, narrowly obovoid conidia. The detailed, illustrated descriptions and notes for each new taxon are provided, and the species of Fuscosporella is reported for the first time in China.